Suicidality and self‐injury with selective serotonin reuptake inhibitors in youth: Occurrence, predictors and timing. (26th August 2021) - Sørensen, Johanne Østerby; Rasmussen, Annette; Roesbjerg, Troels; Verhulst, Frank C.; Pagsberg, Anne Katrine
Abstract: Objective: Meta‐analyses have established a heightened risk of suicidality for youth treated with selective serotonin reuptake inhibitors (SSRIs). The present study investigates the risk and possible predictors of suicidality and non‐suicidal self‐injury (NSSI) associated with SSRI treatment in a clinical sample of children and adolescents. Methods: An observational, longitudinal, retrospective study using a within‐subject study design including in‐ and outpatients aged 0–17 years treated with SSRIs. Data were obtained from digital medical records and prescription software. Results: N = 365 patients were included (64.1% female), mean (SD) age 14.5 (2.04) years, with primary depression, anxiety or obsessive‐compulsive disorder. No suicides occurred. When comparing the 6‐week period immediately prior to versus following SSRI initiation, the patient proportion with broadly defined suicidality decreased (38.5% vs. 24.2%, p < 0.001) while the proportion with suicide attempts was stable (2.8% vs. 2.8%, p = 1.000). The proportion with NSSI decreased statistically non‐significantly (12.4% vs. 8.4%, p = 0.067). Results from individually standardized observation periods were similar; however, the proportion with suicide attempts decreased statistically non‐significantly and the proportion with NSSI decreased significantly. Suicidality during SSRI treatment was associated with previous suicidality (OR[CI] = 6.0 [2.4–14.8], p < 0.001), depression as indication for SSRI treatment (OR[CI] = 2.1 [1.2–3.7], p = 0.01), female sex (OR[CI] = 2.1 [1.1–4.1], p = 0.02) and previous NSSI (OR[CI] = 2.0 [1.2–3.5], p = 0.01). Conclusion: Suicidality was common in youth treated with SSRIs. The patient proportion with overall suicidality decreased, and the proportion with attempted suicide was stable in the weeks following SSRI initiation. Previous suicidality, depression, female sex and previous NSSI are important predictors for suicidality during SSRI treatment in youth.